A Cross-sectional survey on the knowledge and attitudes towards e-waste and its impact on public health among IIUM students-Kuantan campus - Islam, Mohd Aminul; Azad, Abul Kalam; Sunzida, Nushrat Khan (Wolters Kluwer Medknow, 2018)
E-waste is a subset of solid waste and is defined as any solid waste which is generated by individual, educational institution, general institution, industry, housing area or as a household and so many other sources. This survey has led to an enhanced national or local and international awareness of the potential detrimental effects on the environment and public health. Objective: The main objective of this survey is to develop of public awareness about dangerous effect of e-waste on public health and environment. Methods: From the calculated sample size (341), a total of 296 surveys were included in the final analysis. This was a descriptive cross-sectional survey involving with individual users based on a structured questionnaire format with answer sets. Data were analysed using SPSS version 21.0 and excel. Results: The most significant number of respondents came to know about e-waste through internet and friend 36% and 22% while government awareness program and newspapers cover only 16% and 8% of them respectively. Almost all (99.66%) respondents do not know how to dispose e-waste. 86.49 percent of the total respondents agree that as an emerging industrial country Malaysia is at high risk for generating electrical waste where 82.77% are concerned of its related health problem caused. More than 95% of the respondents thinks that individual effort would the effective to reduce e-waste volume by practicing 3R. However, 93.24% of the respondents never got a chance to attend such awareness program because they never knew that there is e-waste awareness programme being conducted by university or community. Conclusion: Based on this survey report, all the respondents think that awareness programme on e-waste should be conducted by the institution to spread negative impact of e-waste on environment and public health. Key Messages: The aim of this study is to make aware about the E-Waste and its impact on Public Health In Malaysia. People in Malaysia should more concern about e-waste due to its huge generation and not proper disposing or lack of disposal system.